Health hazards resulting from the WEEE combustion at illegal e-waste yards in developing countries on the example of Agbogbloshie - Ewa Zieliński; Adriana Wielgus; Katarzyna Sas; Walery Zukow (Kazimierz Wielki University, 2018)
Developing countries do not have legal regulations and adequate infrastructure to safely store and dispose of rubbish therefore in those places waste disposal usually involves burrying or burning. A particular problem in West Africa is the burning of waste electrical and electronic equipment (WEEE) in the e-waste dumping located in Agbogbloshie in the suburbs of the capital of Ghana. As a result of the combustion process, chemical substances hazardous to human health are released into the atmosphere, mosty heavy metals, acid gases, polycyclic aromatic hydrocarbons (PAHs) and dioxins. The paper addresses the problem of health hazards due to the combustion of WEEE in the illegal e-dumping site in Agbogbloshie, Ghana.